Implementation of Online Learning for Grade 3 Students at Madrasah Ibtidaiyah: Implementasi Pembelajaran Daring pada Siswa Kelas 3 di Madrasah Ibtidaiyah - Siti Khoirinatus Sholihah; Nur Maslikhatun Nisak (Academia Open, 2023)
This study investigates the implementation of online learning for grade 3 students at MI MA'ARIF KEDENSARI in response to the COVID-19 pandemic. The aim of this research is to examine the challenges, benefits, and overall effectiveness of online learning in a primary school setting. Qualitative methods, including observation and documentation, were employed to collect data and information. Additionally, interviews were conducted with two teachers and two students to gain insights into the implementation of online learning. The study reveals various obstacles encountered during online learning activities, such as limited access to cellphones and poor signal availability, which hindered student participation. Furthermore, through the interviews, both positive and negative aspects of online learning were identified. These findings have implications for educational institutions and policymakers, emphasizing the need for addressing technological limitations and designing effective online learning strategies for young students. The study contributes to the ongoing discourse on online education and provides valuable insights into the challenges faced during its implementation at the grade 3 level. Highlights: Limited access: The study reveals the challenges faced by grade 3 students in online learning due to limitations in cellphones and poor signal availability. Comprehensive data collection: Researchers utilized qualitative methods such as observation, documentation, and interviews with teachers and students to gather information on the implementation of online learning. Mixed outcomes: The research findings highlight both positive and negative aspects of online learning for grade 3 students, indicating a need for further examination and improvement in the online education process. Keywords: online learning, grade 3 students, implementation, obstacles, positive and negative aspects